Post-reading practices of parents and children ages 3-5 years old at home - Ramos, Rae Ann; Tongson, Excelsa (2012)
Abstract The objectives of the study are to identify the post-reading practices that parents engage in at home with their preschool-aged children (3-5 years old); to categorize these post-reading practices; and to describe the reasons as to why parents choose to do post-reading practices at home. Using stratified random sampling, forty parents from two preschools in Quezon City answered survey questionnaires. Of the forty survey questionnaire respondents, nineteen participated in small group discussions in order to provide depth to their questionnaire responses. Thinking activities were the most popular post-reading activities done by parents and children across ages after reading, followed by Feeling activities, with Doing activities being done the least. The reasons given by parents for engaging in post-reading practices were largely for cognitive development. Some do the practices for language development, socio-emotional development, or moral development reasons. Parent respondents have reported a positive response from their children on post-reading practices, sharing that their children enjoy and look forward to the activities.By engaging in such practices, the respondents have perceived several cognitive development benefits, language development, socio-emotional development, and moral development benefits. The study has shown that post-reading practices are beneficial practices for parents and children and that these must be conducted more often by parents and children.
"March 2012."
Thesis (M.F.L.C.D.)--University of the Philippines Diliman.
Keywords: Children -- Books and reading -- Philippines; Parent and child -- Books and reading -- Philippines; Reading (Early childhood) -- Philippines